Studying the Effect of the Primary Coefficients (X, U) of the Logistic Chaotic Encryption Algorithm Equation on the Performance of X-Ray Medical Image Encryption (Sebha University Conference Proceedings, 2024)
An image encryption method based on the chaotic logistic encryption algorithm was applied on X-ray medical image, using the histogram of the X-ray image and the plot showing the correlation between adjacent pixels to verify the encryption effect of this encryption algorithm. In order to reflect the effect of the algorithm in encrypting image information, use MATLAB to display the encryption. Subsequent image and histogram analysis can intuitively find that the chaotic logistic encryption algorithm has a better effect on encrypting image information, and the statistical data well hides the characteristics of the original image, which can effectively resist statistical attacks based on image pixel values. Image encryption effect and multiple image quality metrics are applied to verify the encryption effect of this encryption algorithm, this method was applied to medical images of the type of X-ray Through the application of a number of image quality standards, the extent of the influence of the parameter X.